Revisão da literatura sobre o Transtorno do Défict de Atenção e Hiperatividade nas revistas nacionais do campo da Terapia Ocupacional - Castro, João Vitor Arnosti de (Universidade Federal de São Carlos, 2023)
The presence of Attention Deficit Hyperactivity Disorder – ADHD, causes difficulties in people's personal and interpersonal lives. As it is a problem that has consequences for behavior, low self-esteem, among other areas, it has received attention from researchers from different fields of knowledge, one of them being Occupational Therapy. The present research aims to identify and describe studies on the topic related to Attention Deficit Hyperactivity Disorder – ADHD present in national journals in the field of occupational therapy. To this end, an integrative literature review was carried out in 4 national journals specific to Occupational Therapy: Revista de Terapia Ocupacional da USP, Cadernos Brasileiros de Terapia Ocupacional, Revista Interinstitucional Brasileira de Terapia Ocupacional and Revista Baiana de Terapia Ocupacional. The data collection stages related to the development of this research were: (1) identification of the theme in the title of each article in the magazine; (2) application of inclusion and exclusion criteria in study abstracts from the aforementioned journals; (3) selection and reading of studies in full accompanied by the extraction of information of interest to the research; (4) interpretation of results and finally, (5) writing of review data. The results were analyzed using quantitative and qualitative approaches. After applying the inclusion criteria, three articles were selected. The period in which the topic in a more comprehensive way is present in national Occupational Therapy journals is between 1992 and 2020, however with the specific term ADHD it is between 2012-2018. The intervention strategies in Occupational Therapy identified by Occupational Therapists demonstrated the importance of knowing and considering aspects of play, the environments of children with ADHD, and their preferences in intervention processes. Finally, the data showed the relationship between ADHD symptoms and the level of assistance required by the child. It is hoped that this study can contribute to the development of new research in the field of ADHD and Occupational Therapy.
Review of the literature on Attention Deficit Hyperactivity Disorder in national journals in the field of Occupational Therapy
Keywords: Terapia ocupacional; Revisão da literatura; Transtorno de Déficit de Atenção e Hiperatividade (TDAH); Occupational therapy; Review of the literature; Attention Deficit Hyperactivity Disorder; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL